PERMAINAN PERAN (ROLE PLAY) UNTUK PEMBELAJARAN SHALAT - Sayed Fachrurrazi; Saiful Afwadi (Teknik Informatika Universitas Malikussaleh, 2013)
Many computer users pay more attention upon computer games, using this kind of computer features make the user able to stay long in fron of computer. The implementation of